Physical and anthropometric profile of international-level Japanese male freestyle wrestlers - Yamashita, D.; Arakawa, H.; Wada, T.; Yumoto, K.; Fujiyama, K.; Nagami, T.; Shimizu, S. (International scientific and professional conference on wrestling: "Applicable research in wrestling", 2017)
PURPOSE: The purpose of the study is aimed to compare physical and anthropometric characteristics of international- and collegiate-level Japanese male freestyle wrestlers, belong to the light weight category. METHODS: Twenty Japanese male freestyle wrestlers belonging to the light weight category (former 55-, 60-, or 66-kg) were categorized into 2 groups. First group composed of 11 international-level wrestlers including 3 Olympic medalists. Second group composed of 9 collegiate-level wrestlers. Body composition was assessed by multi-frequency bioimpedance analysis device with 8-point contact electrodes. Isokinetic concentric knee and hip extension and flexion torque were measured using an isokinetic dynamometer. Morphological data was obtained by means of a three-dimensional scanning method. Twelve circumferences (neck, upper arms, forearms, thighs, lower legs, chest, waist, and hip) and four lengths (arms and legs) were computed. Simple reaction time was evaluated using an electronic device. Comparisons of these variables between the two groups were performed by unpaired t-tests. RESULTS: The results showed there was no difference in body composition, body circumferences, and limb length between groups other than chest circumference (p < 0.05). There was no difference in hip and knee strength and simple reaction time between groups. CONCLUSIONS: These results suggested that chest circumference is important to become an international-level wrestler. Also, other aspects such as multi-joint motor skills, technical and/or tactical skills may be important for international-level wrestlers.